Analisis Pengembangan Sumber Daya Manusia, Kerjasama Tim dan Kreativitas Terhadap Kinerja Karyawan PT. Mavens Mitra Perkasa Malang - achmad taufiq nurrohman; Hadi Sunaryo; m Ridwan Basalama (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to describe the development of human resources, teamwork, creativity, employee performance; analyze the effects of human resource development variables, teamwork, and creativity simultaneously on employee performance; analyze the effect of human resource development on employee performance; analyze the effect of teamwork on employee performance, and analyze the effect of creativity on employee performance.The method used in this study is a quantitative research method with a descriptive approach and carried out at PT. Mavens Mitra Perkasa Malang with a population of 44 employees. Data collection techniques using a questionnaire with the measurement using a Likert scale. Data analysis techniques used were validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, F hypothesis test, t hypothesis test, and coefficient of determination test.The results of this study indicate that human resource development, teamwork, and creativity simultaneously affect employee performance. Human resource development influences employee performance. Teamwork influences employee performance. Creativity affects employee performance..Keywords: Human Resource Development, Teamwork, Creativity, Employee Performance